Dampak Pelatihan Kesehatan Gigi dan Mulut Pada Siswa Sekolah Dasar Dalam Meningkatkan Status Kebersihan Mulut Siswa - Weni, Mustika; Mauladani , Muhammad Firqin; Wahidan, Fikri; Salsabila, Wanda Ayu; Yuniarni, Ervina (JPM: Jurnal Pengabdian Masyarakat, 2025)
Dental caries is one of the most common oral health problems in society. One of the factors suspected to contribute to the occurrence of dental caries is the habit of brushing teeth. This program aims to increase students' knowledge about the importance of dental and oral care and train them in correct tooth brushing techniques. This activity began with counseling on dental health problems that children often face, such as cavities due to bad habits and high sugar consumption. Furthermore, students were given practical training on how to brush their teeth effectively. After the counseling, data collection was continued with a questionnaire to determine children's tooth brushing habits and the incidence of tooth decay. The results of the training showed that students were very enthusiastic and were able to understand and practice the correct tooth brushing technique. The results of the study: the habit of brushing teeth of elementary school children in the category of irregular brushing of teeth was 15 students (34.1%) of respondents from 44 respondents who were sampled. And the occurrence of tooth decay in children was 28 students (63.6%) of 44 respondents who were sampled. The results of the analysis of the relationship between tooth brushing habits and the occurrence of tooth caries. The analysis using the Chi-square test showed a P-Value = 0.361, indicating no significant relationship between tooth-brushing habits and the occurrence of dental caries. This suggests that other factors, such as dietary patterns, particularly frequent consumption of sugary foods like chocolate or candy, may have a greater influence on dental caries occurrence. Therefore, it is necessary to educate students about the importance of maintaining oral hygiene and reducing sugary food consumption to prevent dental caries.